STRATEGI MARKETING DALAM UPAYA MENINGKATKAN KEDATANGAN WISATAWAN DI DISTRIK DILI TIMOR LESTE - Ida Ayu Trisna Wijayanthi; Ida Bagus Gede Udiyana; Sendia Maria Verdial Vieira (Forum Manajemen STIMI Handayani Denpasar, 2018)
The importance of the tourism industry in the economy of the country, and to improve the economy of the country of Timor-Leste, this study is trying to implement the appropriate marketing management strategy to increase tourist visits, especially in Dili District. So the formulation of the problem studied in this study is “How is the Marketing Strategy in Efforts to Increase Tourist Arrivals in the Dili District of East Timor and what factors affect the management of tourism in the Dili District of East Timor”. The purpose of this study are (1) To know the marketing strategy in an effort to increase tourist arrivals in the Dili District of East Timor. (2) To know what factors affect the management of tourism in the Dili District of East Timor. Data analysis technique used in this research is descriptive analysis using SWOT analysis approach and marketing mix analysis. Based on the results of the study, it can be concluded that the Marketing Strategy conducted in Dili District of East Timor is emphasized on 7 P that is Product, Price, Place, Promotion, People, Process, Physical Evidence